Novel Bi-SBA-15 derived rice husk for iodine adsorption from off-gas stream - Ahmed Al-Mamoori; Israa Sh. Mohammed; Huda D. Abdul Kader; Abdullah Mohammed Al-sadoon; Hasan Sh. Majdi (Results in Chemistry)
Nuclear energy is considered a reliable renewable energy source although it releases some radioactive wastes that are not friendly to the environment. This necessitates the development of such eco-friendly, abundant, and efficient materials to control these radioactive wastes, thus rendering this sort of energy more sustainable. In this research, Bismuth-SBA-15 derived from rice husk waste material was synthesized and then evaluated for the adsorption of iodine (129I) that is disposed from nuclear waste off-gas stream. The optimum bismuth loading (20 wt. %Bi-SBA-15) exhibited as much as 3956 mg/g at 200 °C of iodine capture capacity which is 18.4-fold of the commercial silver-mordenite adsorbent material. This finding represents the highest value reported in the literature for bismuth-based adsorbent materials for gas phase adsorption. Three different temperatures (100, 150, and 200 °C) were performed for iodine capture and the material exhibited as high as 3291 and 3956 mg/g for 150, and 200 °C respectively which is close to the spent fuel waste temperature of ∼140 °C. The material durability was also tested under three consecutive adsorption-desorption cycles and attained 82 % of its initial cycle under iodine exposure for 18 h. The interaction of iodine with bismuth was in the form of the highly stable compound (BiOI) which is advantageous for further iodine immobilization process. The materials exhibited relatively stable iodine capture capability after three consecutive cycles. Further investigation was also performed to study the physiochemical characterization such as XRD, FT-IR, BET-PSD, SEM-EDX, TEM, XPS, and TA analysis. The current study suggests that Bismuth-SBA-15 derived from rice husk waste material could be a potential candidate for the adsorption of iodine (129I).